Fetal Ganglioneuroblastoma: A Rare Entity with Antenatal Diagnosis and Postnatal Follow Up - Varshney, Alok; Kapoor, Aakriti; Kaur, Shina; Kapoor, Tushar; Kapoor, Aakaar; Kapoor, Apurva; Kapoor, Ravi (Journal of Fetal Medicine, 2024)
Fetal abdominal masses can be challenging to counsel due to uncertain diagnosis and outcomes. We report a case of a midline upper retroperitoneal mass found incidentally during a routine third trimester ultrasound. Despite not being a suprarenal mass, ultrasound and magnetic resonance imaging indicated neuroblastoma prenatally. With the generally favorable prognosis for prenatally diagnosed neuroblastomas, expectant counseling was given. Postnatal imaging and biopsy confirmed ganglioneuroblastoma, a rare subtype. A conservative approach was taken, and after initial growth, the mass spontaneously regressed 5 months after birth, nearly resolving by 8 months.
Keywords: antenatal; fetal; ganglioneuroblastoma; neuroblastoma; tumor